2015
DOI: 10.7454/efi.v61i3.512
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Firm Innovation in Indonesia: The Role of Institutions and Access to Finance

Abstract: This paper investigates the determinants of firm innovation in Indonesia. Using quality of local regulations index constructed by the Indonesia’s Regional Autonomy Watch (KPPOD) as measure of institutions, We found that better institutional quality at the local level was associated with more innovation and that firms experiencing major obstacle in access to finance were less likely to innovate. Access to finance is more critical for small and medium enterprises (SMEs) whereas institutional quality is more impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 71 publications
2
18
0
3
Order By: Relevance
“…In this regards, Kirkpatrick et al (2006) concluded that the quality of regulatory framework and foreign investment is highly related. They also observed that due to weak government regulations foreign investors may reluctant to investment in the large investment projects like R&D. Similarly, Mahendra et al (2015) found evidence that good regulatory quality and access to finance have positive impact on innovation. Although, Blind et al (2017) stated that the relation between regulations and innovation may differ due to market environments, they found that regulations have positive influence on innovation in low uncertain markets while opposite effects in high uncertain markets.…”
Section: Theory and Hypothesesmentioning
confidence: 97%
See 1 more Smart Citation
“…In this regards, Kirkpatrick et al (2006) concluded that the quality of regulatory framework and foreign investment is highly related. They also observed that due to weak government regulations foreign investors may reluctant to investment in the large investment projects like R&D. Similarly, Mahendra et al (2015) found evidence that good regulatory quality and access to finance have positive impact on innovation. Although, Blind et al (2017) stated that the relation between regulations and innovation may differ due to market environments, they found that regulations have positive influence on innovation in low uncertain markets while opposite effects in high uncertain markets.…”
Section: Theory and Hypothesesmentioning
confidence: 97%
“…According to Krammer (2015), "In practice, measuring institutions is a daunting task". In this regard, Mahendra et al (2015) stated that it is difficult to measure institutional variables as each country and region may have different understanding and perceptions on what institutions are. Dunning (2006) has also pointed out the differences in country level institutional variables.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…In report of Aubert (2015), finance is an essential factor to promote innovation activities for low technology SMEs and micro enterprises. Mahendra, Zuhdi and Muyanto (2015) also stated that access to finance is an important factor of innovation level in organization. However, financing for innovation is a more difficult investment because innovative projects always have higher risks than others.…”
Section: Hypothesismentioning
confidence: 99%
“…For instance, van Uden et al (2014) analyzed the impact of human capital innovation in developing countries (Kenya, Tanzania, and Uganda) using data from the Enterprise Surveys of the World Bank and found that human capital spurs innovation. Mahendra et al (2015) also argued that human capital affects innovation abilities of enterprises in Indonesia. Mahendra et al (2015) further showed that different combinations of human capital affect innovative output depending on the context in which these combinations are implemented (manufacturing or service sector).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mahendra et al (2015) also argued that human capital affects innovation abilities of enterprises in Indonesia. Mahendra et al (2015) further showed that different combinations of human capital affect innovative output depending on the context in which these combinations are implemented (manufacturing or service sector). Moreover, Audretsch et al (2016) added that academic-based human capital encourages innovativeness of enterprises while business-based human capital does not play a role.…”
Section: Literature Reviewmentioning
confidence: 99%